2015
DOI: 10.1371/journal.pone.0136202
|View full text |Cite
|
Sign up to set email alerts
|

Barriers and Facilitators for Type-2 Diabetes Management in South Asians: A Systematic Review

Abstract: ObjectiveAlthough South Asian populations have among the highest burden of type 2 diabetes in the world, their diabetes management remains poor. We systematically reviewed studies on South Asian patient’s perspectives on the barriers and facilitators to diabetes management.MethodsWe conducted a literature search using OVID, CINHAL and EMBASE (January, 1990 –February, 2014) evaluating the core components of diabetes management: interactions with health care providers, diet, exercise, and medication adherence. S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

23
217
1
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 187 publications
(251 citation statements)
references
References 40 publications
23
217
1
2
Order By: Relevance
“…Celebrating with family or friends is a problem because patients often do not want to tell people in their environment about their health problems; other problems include being alone and not having support, which can lead to depression and a lack of motivation (Ahrani et al., ; Mellon et al., ). Similar results were also obtained in a systematic review on barriers and facilitators for the management of type 2 diabetes, which identified social pressure at social events, together with circumstances that can lead people to prepare traditional cuisine dishes and associated cultural issues (Sohal, Sohal, King‐Shier, & Khan, ). Simultaneously, family support can be a facilitating factor when meals are prepared at home (Ahrani et al., ; Mellon et al., ; Oh et al., ; Sohal et al., ).…”
Section: Discussionsupporting
confidence: 72%
See 2 more Smart Citations
“…Celebrating with family or friends is a problem because patients often do not want to tell people in their environment about their health problems; other problems include being alone and not having support, which can lead to depression and a lack of motivation (Ahrani et al., ; Mellon et al., ). Similar results were also obtained in a systematic review on barriers and facilitators for the management of type 2 diabetes, which identified social pressure at social events, together with circumstances that can lead people to prepare traditional cuisine dishes and associated cultural issues (Sohal, Sohal, King‐Shier, & Khan, ). Simultaneously, family support can be a facilitating factor when meals are prepared at home (Ahrani et al., ; Mellon et al., ; Oh et al., ; Sohal et al., ).…”
Section: Discussionsupporting
confidence: 72%
“…Similar results were also obtained in a systematic review on barriers and facilitators for the management of type 2 diabetes, which identified social pressure at social events, together with circumstances that can lead people to prepare traditional cuisine dishes and associated cultural issues (Sohal, Sohal, King‐Shier, & Khan, ). Simultaneously, family support can be a facilitating factor when meals are prepared at home (Ahrani et al., ; Mellon et al., ; Oh et al., ; Sohal et al., ).…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…However, few studies have investigated the factors associated with patient participation in prescribed diabetes education programs [14151617]. …”
Section: Introductionmentioning
confidence: 99%
“…High BMI was the only demographic factor associated with the uptake of screening. This may relate to hesitancy in this population to make lifestyle changes to manage their diabetes risk, or obesity may be a proxy marker for deprivation.More than 40% of our cohort were from an Asian background, in whom language and communication may be a barrier to understanding information given by healthcare professionals [7]. Postnatal diabetes leaflets written in different languages may make the information accessible.…”
mentioning
confidence: 99%